Konstrukčně-výrobní řešení upínacího přípravku - Okáč, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Diplomová práce se zabývá různými aspekty konstrukčně - výrobního řešení upínacího přípravku v podmínkách malé výrobní firmy. V diplomové práci jsou rozebrány problémy, se kterými se autor práce při malosériové a kusové výrobě setkává. Důraz je kladen zejména na efektivitu a ekonomičnost celého výrobního procesu.

The thesis deals with various aspects of the structure - manufacturing solutions fixture in terms of small manufacturing firm. In the thesis are discussed problems which the author of the thesis with small-scale production meets. A substantial part of the thesis is also made by comparation of the production of small series production and large series. Emphasis is placed on efficiency and economy of the entire production process.
Construction and Manufacture of a Clamping Device
Keywords: upínací přípravek; výroba; technologičnost konstrukce; obráběcí centrum; fixture; manufacture; technology; CNC; machining